Work‐related post‐traumatic stress symptoms in obstetricians and gynaecologists: findings from INDIGO, a mixed‐methods study with a cross‐sectional survey and in‐depth interviews. (27th January 2020) - Slade, P; Balling, K; Sheen, K; Goodfellow, L; Rymer, J; Spiby, H; Weeks, A
Abstract : Objectives: To explore obstetricians' and gynaecologists' experiences of work‐related traumatic events, to measure the prevalence and predictors of post‐traumatic stress disorder (PTSD), any impacts on personal and professional lives, and any support needs. Design: Mixed methods: cross‐sectional survey and in‐depth interviews. Sample and setting: Fellows, members and trainees of the Royal College of Obstetricians and Gynaecologists (RCOG). Methods: A survey was sent to 6300 fellows, members and trainees of RCOG. 1095 people responded. Then 43 in‐depth interviews with trauma‐exposed participants were completed and analysed by template analysis. Main outcome measures: Exposure to traumatic work‐related events and PTSD, personal and professional impacts, and whether there was any need for support. Interviews explored the impact of trauma, what helped or hindered psychological recovery, and any assistance wanted. Results: Two‐thirds reported exposure to traumatic work‐related events. Of these, 18% of both consultants and trainees reported clinically significant PTSD symptoms. Staff of black or minority ethnicity were at increased risk of PTSD. Clinically significant PTSD symptoms were associated with lower job satisfaction, emotional exhaustion and depersonalisation. Organisational impacts included sick leave, and 'seriously considering leaving the profession'. 91% wanted a system of care. The culture in obstetrics and gynaecology was identified as a barrier to trauma support. A strategy to manage the impact of work‐place trauma is proposed. Conclusions: Exposure to work‐related trauma is a feature of the experience of obstetricians and gynaecologists. Some will suffer PTSD with high personal, professional and organisational impacts. A system of care is needed. Tweetable abstract: 18% of obstetrics and gynaecology doctors experience post‐traumatic stress disorder after traumatic events at work. Tweetable abstract: 18% of obstetrics and gynaecology doctors experience post‐traumatic stress disorder after traumatic events at work.